Powder-based (CuGa1−yIny)1−xZn2xS2 solid solution photocathodes with a largely positive onset potential for solar water splitting. Issue 9 (12th April 2018) - Hayashi, Toshio; Niishiro, Ryo; Ishihara, Hitoshi; Yamaguchi, Masaharu; Jia, Qingxin; Kuang, Yongbo; Higashi, Tomohiro; Iwase, Akihide; Minegishi, Tsutomu; Yamada, Taro; Domen, Kazunari; Kudo, Akihiko
Abstract : (CuGa1− y In y )1− x Zn2 x S2 has arisen as a highly efficient powder-based photocathode for water splitting under simulated sunlight irradiation. Abstract : Photoelectrochemical water splitting has attracted much attention in recent years as an alternative energy source. However, there have been several significant issues such as low efficiency, high cost and less scalability for its practical application. Here, we show that (CuGa1− y In y )1− x Zn2 x S2 (CGIZS)-based photocathodes fabricated with a particle transfer method exhibited a photocurrent of 4.5 mA cm −2 at 0.6 V vs. RHE along with a largely positive onset potential of 1.0 V vs. RHE under simulated sunlight (AM 1.5G) and an initial solar-to-hydrogen energy conversion efficiency of 1.1% was obtained with photoelectrochemical water splitting using a two-electrode cell composed of the CGIZS-based photocathode and a BiVO4 -based photoanode. CGIZS used for the particle transfer method was obtained in a powder state with high crystallinity by a flux method using a molten-salt of LiCl–KCl, and also formed solid solutions with a chalcopyrite single phase structure in a wide range of Ga/In ratios and Zn contents, in which the absorption edges of photocatalysts were tunable up to 880 nm.